The Effect of Employee Support Policy Effectiveness, Collaborative Leadership, and Work Rewards on Organizational Innovation in the Manufacturing Industry in West Java - Ariesmansyah, Andre; Arisanti, Ivon; Rahmawati, Riska (West Science Social and Humanities Studies, 2024)
This study investigates the effect of employee support policy effectiveness, collaborative leadership, and work rewards on organizational innovation in the manufacturing industry in West Java. Using a quantitative analysis approach, data was collected from 135 employees across various manufacturing firms. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed to analyze the relationships between the variables. The results reveal significant positive relationships between employee support policy effectiveness, collaborative leadership, work rewards, and organizational innovation. The findings underscore the importance of prioritizing employee well-being, fostering collaborative leadership practices, and implementing effective reward systems to promote innovation within organizations. These insights offer valuable implications for managerial practices and strategies aimed at enhancing organizational innovation and competitiveness in the manufacturing sector.